Penatalaksanaan Pijat Oketani dan Kompres Daun Kubis dengan Masalah Ketidakefektifan Pemberian Asi pada Ibu Post-Partum di Kelurahan Bulakrejo - Anggita Dwi Prastiwi; Tutik Rahayuningsih (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
The puerperium is a recovery period that starts after the placenta is born and ends when the uterus returns to its pre-pregnancy state. One of the physiological changes that occur during the puerperium is lactation, such as the presence of breast milk. One of the efforts to overcome breast milk is by using oketani massage and compressing cabbage leaves. This study aims to describe the management of oketani massage and cabbage leaf compresses with the problem of ineffective breastfeeding in post-partum mothers. The qualitative descriptive research design uses case studies (case study research) with a nursing process approach. The technique of taking the subject of non-probability sampling with a purposive sampling approach. The research data obtained that the milk had not come out, the breasts were full and painful, the mother felt that she had not succeeded in breastfeeding, the rooting reflex was weak, both breasts looked tense, the nipples were inward and dirty, there was a dam of milk, tenderness in both breasts, 0cc milk production. Nursing diagnosis of ineffective breastfeeding related to insufficient milk supply. Nursing action of oketani massage and cabbage leaf compresses for 7 days, every morning and evening for 20-30 minutes. Evaluation of the action of oketani massage and cabbage leaf compresses can increase milk production from 0cc to 80-120cc. The action of oketani massage and cabbage leaf compresses can overcome nursing problems ineffective breastfeeding related to insufficient milk supply.